Catgutpuncture and ozone therapy combined treatment in vulgar psoriasis. Lucia Íñiguez Landín Clinical Surgical Hospital. 2019- 2021 - Lisbet López Mulet; Yaima Quintana Rojas; Annarelis Pérez Pupo (Medisur)
Background: psoriasis affects approximately 2 % of the world population, with extensive biopsychosocial repercussions. Objective: to determine the effectiveness of the combined catgutpuncture-ozone therapy treatment in patients with psoriasis vulgaris. Methods: quasi-experimental intervention study of the type before and after without a control group carried out at the Lucia Íñiguez Landín Hospital, from April 2019 to 2021. 55 patients were the population; 29 patients were the sample who met the inclusion criteria. A multivariate analysis of absolute and relative frequencies was performed. To evaluate the effectiveness of the treatment, the statistical test of proportions’ difference was used with a confidence level of 95%, being considered statistically significant. Results: the female sex and the age group of 40 to 49 years old predominated. Kidney Yin and liver Xue insufficiency syndromes was the most representative. It was possible to reduce the severity of the disease in almost all of them. Adverse reactions to the therapies used were minimal. Conclusions: the combined treatment was considered partially effective.